Persepsi Dan Preferensi Tinggal Masyarakat Pada Area Sempadan Sungai (Studi Kasus : Kelurahan Bailang Kota Manado - Gabriel Purnama; Sri Legowo Wignyo Darsono; Ana Nugranah Chaidar (Departement of Mathematics Education, 2024)
People who still live in the area around the river, even after the flood disaster is a matter of concern. The perceptions and preferences of the community are very influential when choosing a place of residence. Basically, these perceptions and preferences are shaped by their knowledge or understanding of the objects that will be perceived, as well as the main reason people choose their current residence, which in this study is the river border area in the Manado City Bailang Kelurahan. The majority of the inhabitants of the river border region that suffered flooding in January 2023 chose to remain in the rivers border area, even though they were aware of the dangers that might arise later on. The aim of this research is to find out the perceptions and preferences of the people who live around the border of the Bailang river so that they can continue to live there. This research uses quantitative methods with descriptive analysis. The conclusion derived from the perceptions and preferences of the population is that they chose to settle in the river boundary area in the Bailang District of the City of Manado, because many local people do not understand about river border areas, the establishment of river borders, the distance of establishing river lines on either river-boundary or non-border river, then does not understand the purpose of the rivers border area and the people hear from others information obtained about rivers boundaries area and some have also heard of socialization from the government. People who choose to stay in the River Border Area because there is no other land for them to build houses and also in the place where they now have cheap land prices.